MACROFUNGAL DIVERSITY IN DIFFERENT VEGETATION COMPOSITIONS IN TEGHARI COMMUNITY FOREST, KAILALI, WEST NEPAL - Kausalya Joshi; Hari Sharan Adhikari; Hari Prasad Aryal; Laxmi Joshi Shrestha (BIOTROPIA, 2022)
Macrofungi are high-value forest resources that have functionally significant roles in the forest ecosystem. The macrofungal community of three different vegetation compositions, i.e., Sal (Shorea robusta) Forest, Tropical Deciduous Riverine Forest, and Tropical Evergreen Forest of Teghari Community Forest were investigated. Systematic random sampling was made where 60 plots (10 x 10 m) were laid in all different forest types (20 plots in each). A total of 102 macrofungi species were reported belonging to 36 families. Polyporaceae (17 species) was the largest family followed by Tricholomataceae (13 species) and saprophytic fungi were more frequent than mycorrhizal and parasitic fungi. The tropical evergreen forest was rich in macrofungi (59 species) followed by sal forest (40 species) and tropical deciduous riverine forest (38 species). Macrofungal diversity was directly related to surrounding host species. Similarly, increased soil moisture and canopy cover intensified the abundance of saprophytic fungi. The species richness was increased with increasing organic carbon, canopy, moisture, pH, and litter cover. However, soil nitrogen, phosphorus, and potassium were less significant in affecting species richness. Also, the disturbance was negatively correlated with the species richness of macrofungi. This study highlights the hidden diversity which is necessary for the conservation of macrofungi, to optimize forest ecosystem integrity and resilience against biotic and abiotic agents